Ketersediaan Kedelai Berdasarkan Peramalan Produksinya dan Beberapa Kendala serta Permasalahannya di Indonesia - Nugraha, Dedi; Wardana, I Putu; Adnyana, Made Oka (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
Soybean take importance role as source of legumes protein for Indonesian people’s because has lower price compared with other source of protein. Soybean demand contiunously increase because population growth and development of foodindustry’s, while production growth is slowly declining (leveling off) campared to it’s demand. Soybean production’s in 2013 only 0,78 million ton, while it’s demand is 2,9 millions ton, so need import about 2.12 million tons to meet the demand. This study aims to establish a model for predicting soybean production in relationship with constraint and it’s problem as a factor of its boundary. This study used the technique of forecasting with using time series data. Best model selected will be used to estimate soybeanproduction’s. Selection of the best model using criteria Mean Absolute Percent Error (MAPE), Root Mean Square Error (RMSE), and Akaike Information Criteria (AIC). Best model selected is ARIMA (1,1,1). Based on result of forcasting, number of soybean production’s on 2022 is 0,994 million tons. Though has productivity with increasing trend, but it’s not significant, so the production still low compared to it’s demand. Generally, decline of production caused by reduction of harvest area as one of less competitive crop compared with other secondary crops (palawija), and high biotic and abiotic pressure.